Serial Pleasures: The Influence of Television on the Victorian Novel - Plotz, John (Romanticism and Victorianism on the Net, 2013)
The contemporary success of serial television as a dominant long-form narrative artwork presents both perils and possibilities for critics interested in analogous forms in previous eras. TV dramas that viewers can follow from season to season generate a sustained, often years-long, engagement between viewer and depicted world, a very different relationship between viewer and artwork from that which governed viewer relations to pre-TV Hollywood film—or indeed to the Victorian novel, even when serialized. Broad issues of contingency and intention, as well as more nuanced questions of ensemble participation and commercial broadcasting logic separate serial TV from the long-form narratives of the nineteenth century. In offering up parallels between how serialization worked in long-form narrative arts of previous eras and how serial television works now we risk overlooking how those structural differences shape the meaning of any particular work.